Pendanaan dalam Pencapaian Akses Universal Air Minum di Indonesia - Sudarsono, Ratria Anggraini; Nurkholis, Nurkholis (Jurnal Ekonomi dan Pembangunan Indonesia, 2020)
RPJMN 2015–2019 mandates universal access of drinking water in 2019. This study analyzes the policy using panel data regression. Random Effect Model (REM ) shows funding, per capita Gross Regional Domestic Product (GRDP ), and population density explain the water coverage of 23.57%, while the rest are explained by variables outside the model. Gross Regional Domestic Product (PDRB) per capita has the biggest impact on coverage, followed by Population Density. On funding, central government’s budget significantly has the highest impact, followed by local government’s budget (APBD), while others aren’t significant. Investment has positive effect, but high per capita investment may not provide high coverage. The coverage in 2019 based on unit-cost calculation is 80.21%, universal access target isn’t reached.